2007
DOI: 10.1007/s11102-007-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin in neuroendocrine organs and tumours

Abstract: Ghrelin is a 28 amino-acid hormone with multiple functions. It is predominantly produced by the stomach but has also been detected in other organs, including the small intestine, pancreas, hypothalamus and pituitary, as well as in the immune system and almost every other normal human tissue examined. It is also present in neuroendocrine tumours, pituitary adenomas, endocrine tumours of the pancreas, breast tumours, and thyroid and medullary thyroid carcinomas. Ghrelin is a brain-gut peptide with growth hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 133 publications
3
17
0
Order By: Relevance
“…[21][22][23][24] Ghrelin is synthesized mainly in the upper third of the stomach with direct and indirect effects in the area postrema, the nucleus of the solitary tract, the nucleus of hypothalamus, and the brainstem, but it also may have direct and indirect metabolic effects on cells outside the central nervous system. [25][26][27][28][29][30][31][32] Figure 2. (Top) The appetite visual analog score is illustrated in patients who were randomized to receive high-dose (n ¼ 17) or low-dose (n ¼ 14) ghrelin on an intent-to-treat basis at all available registrations (high-dose ghrelin, n ¼ 42; low-dose ghrelin, n ¼ 30; P < .002).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Ghrelin is synthesized mainly in the upper third of the stomach with direct and indirect effects in the area postrema, the nucleus of the solitary tract, the nucleus of hypothalamus, and the brainstem, but it also may have direct and indirect metabolic effects on cells outside the central nervous system. [25][26][27][28][29][30][31][32] Figure 2. (Top) The appetite visual analog score is illustrated in patients who were randomized to receive high-dose (n ¼ 17) or low-dose (n ¼ 14) ghrelin on an intent-to-treat basis at all available registrations (high-dose ghrelin, n ¼ 42; low-dose ghrelin, n ¼ 30; P < .002).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports of pancreatic tumors with ghrelin expression (Rindi et al 2002b, Volante et al 2002, Leontiou et al 2007 suggest that ghrelin could be a potential tumour marker to search for in the blood samples, although one report was unable to detect differences in plasma ghrelin between patients with ghrelin-expressing tumours and controls (Corbetta et al 2003), it has been suggested that patients with malignant gastric endocrine tumours should be investigated for ghrelin production (Tsolakis et al 2004). The potential for ghrelin as a novel tool for detecting previously silent tumours is intriguing and needs further investigation.…”
Section: Clinical Importance Of Islet Ghrelinmentioning
confidence: 99%
“…The appetite-stimulating (orexigenic) hormone ghrelin is primarily released from the stomach and may promote carcinogenesis and tumor growth through its actions via its receptor that acts as a growth hormone secretagogue. It has subsequently been proposed to have a possible role in the development of neuroendocrine tumors, 108 gastrointestinal tumors 109 and prostate cancer. 110 There are a wide range of studies on metabolic surgery demonstrating the modulation and decrease of ghrelin levels after surgery, 12,111 which may contribute to decreased tumor growth and carcinogenesis in a subset of patients.…”
Section: Gut Hormonesmentioning
confidence: 99%